Prognostic Impact of Hyaluronan and Its Regulators in Pancreatic Ductal Adenocarcinoma - Cheng, Xiao-Bo; Sato, Norihiro; Kohi, Shiro; Yamaguchi, Koji (PLOS ONE, 2013)
BackgroundAlthough pancreatic ductal adenocarcinoma is characterized by an abundant stroma enriched with hyaluronan (HA), the prognostic impact of HA and its regulators remains unknown. MethodsUsing immunohistochemistry, expression patterns of HA and its regulators, including a synthesizing enzyme (HAS2), and a degrading enzyme (HYAL1) were investigated in patients who received surgical resection. The prognostic significance of these markers and other clinicopathological variables was determined using univariate and multivariate analyses. The HA levels were determined quantitatively by enzyme-linked immunosorbent assay (ELISA). ResultsWe found that strong expressions of HA (P=0.008) and HAS2 (P=0.022) were significantly associated with shorter survival time after surgery. By contrast, weak expression of HYAL1 was significantly associated with poor survival (P=0.001). In multivariate analysis, tumor stage (hazard ratio (HR)=2.76, 95% confidence interval (CI): 1.14-6.66 P=0.024), strong HA expression (HR=6.04, 95%CI: 1.42-25.69 P=0.015), and weak HYAL1 expression (HR=3.16, 95%CI: 1.19-8.40 P=0.021) were independent factors predicting poor survival. ELISA revealed higher concentration of HA in pancreatic cancer tissues than in normal pancreatic tissues (P=0.001). ConclusionThese findings suggest, for the first time, that HA and its regulators may have prognostic impact in patients with pancreatic cancer.